If You Go Down to the Woods Today: Infants' Distress During a Teddy Bear's Picnic in Relation to Peer Relations and Later Emotional Problems. (24th November 2016) - Hay, Dale F.; van Goozen, Stephanie H. M.; Mundy, Lisa; Phillips, Rebecca; Roberts, Siwan; Meeuwsen, Mirjam; Goodyer, Ian; Perra, Oliver
Abstract : Infants' emotional reactions to an unusual event were assessed at a simulated birthday party during which two costumed characters enacted a Teddy Bear's Picnic. Two hundred and fifty‐eight firstborn infants in a representative British community sample were observed at a mean age of 12.8 months in the presence of their parents and other participating families, in a laboratory sitting room decorated with balloons and banners. The picnic scenario was followed by free play with the other participating infants. At a mean of 36 months of age, mothers, fathers, and another informant who knew the child well completed the Child Behaviour Check List (CBCL). The majority of infants showed no vocal distress during the picnic scenario. A minority of infants expressed strong distress, which was correlated with elevated heart rate and production of cortisol. Infants who were not distressed were more likely to direct social behavior to their peers and especially likely to use physical force against peers. In comparison with strongly distressed and nondistressed infants, those who had shown mild distress during the picnic scenario were least likely to manifest later emotional problems. This pattern was particularly marked for boys. Taken together, the findings indicate that infants' strong distress during naturalistic encounters that are meant to be entertaining can suppress sociability and might indicate risk for subsequent emotional problems.